Peran Orang Tua Mempersiapkan Anak Usia Dini Dalam Menghadapi Perubahan di Era New Normal - Dinita Vita Apriloka; Mardi Fitri (Jurusan Pendidikan Islam Anak Usia Dini UIN Sunan Gunung Djati Bandung, 2021)
Parents are the initial foundation for the continued growth and development of early childhood. Early childhood is an essential period or golden age in which early childhood is an excellent imitator. With the current situation of the COVID-19 pandemic around the world, including Indonesia, the role of the family, including parents, is very important. This study aims to determine how the role of parents in preparing early childhood for the changes in the new normal era. The method used in this research is descriptive quantitative research with the method of interviewing parents and observing children's daily habits. The results showed that the role of parents in facing the new normal era requires a lot of strategies which make children's activities fun so that children do not feel bored and children can adapt to their new habits, barriers for parents in preparing new habits with regard to facilities and the situation and condition of the child's parents. early age.